2011
DOI: 10.1016/j.tjog.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous use of mifepristone and misoprostol for early pregnancy termination

Abstract: Concurrent administration of oral mifepristone 200mg and vaginal misoprostol 600μg is an efficacious regimen for medical abortion of pregnancies up to 49 days of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However in the study by Li YT et al, the mean drug abortion interval was found to be 5.8 hours which is not similar to the results. 8 The side effects in terms of nausea and vomiting were significantly less with buccal route of Misoprostol as compared to vaginal route of Misoprostol. This was found to be similar to the study by Geetika G et al, and also similar to the findings in the study by Alam A et al, Shivering and fever was less in women who took buccal Misoprostol as compared to women taking vaginal Misoprostol.…”
Section: Discussionmentioning
confidence: 90%
“…However in the study by Li YT et al, the mean drug abortion interval was found to be 5.8 hours which is not similar to the results. 8 The side effects in terms of nausea and vomiting were significantly less with buccal route of Misoprostol as compared to vaginal route of Misoprostol. This was found to be similar to the study by Geetika G et al, and also similar to the findings in the study by Alam A et al, Shivering and fever was less in women who took buccal Misoprostol as compared to women taking vaginal Misoprostol.…”
Section: Discussionmentioning
confidence: 90%
“…To create a more accessible medical-abortion service, British Pregnancy Advisory Service (BPAS) — a non-profit abortion provider with 60 clinics in England and Wales— introduced the option of simultaneous administration of mifepristone and misoprostol in 2015. Prior research shows that simultaneous dosing is effective for early medical abortion, although the rate of side effects may be higher, and the need for more than one dose of misoprostol to achieve a complete abortion may arise more frequently, than with a 24-hour interval between medications (8, 9, 10, 11, 12). To avoid a second clinic visit, however, women may still prefer simultaneous dosing where home-use of misoprostol is restricted, despite potential differences between regimens.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Overall it has been shown that an interval of approximately 6 hours between mifepristone and misoprostol results in equal efficacy as 24-48 hours in first-trimester abortion. There have been several studies specifically assessing the interval between mifepristone and misoprostol administration with respect to abortion outcome.…”
Section: Methods Of Study Selectionmentioning
confidence: 99%